Residual effect of sewage sludge fertilization on sunflower yield and nutrition - Hermann C. de Albuquerque; Geraldo R. Zuba Junio; Regynaldo A. Sampaio; Luiz A. Fernandes; Fabiano B. S. Prates; Nelson M. B. do Amaral Sobrinho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACTThis study aimed to evaluate the residual effect of sewage sludge fertilization on yield and nutrition of sunflower in its second cycle. The experiment was carried out from April to August 2012. The treatments consisted of four doses of sewage sludge (0, 10, 20 and 30 t ha-1, dry basis) applied in the first cycle of sunflower, distributed in a randomized block design, with six replicates. Sunflower stem diameter, plant height, capitulum diameter and yield increased with the increment in sewage sludge doses, with maximum values observed with the dose of 30 t ha-1. The contents of calcium and magnesium in the soil, pH, sum of bases, effective and potential cation exchange capacity and base saturation increased, while potential acidity and the contents of manganese and iron in the leaves decreased, with the increment in the residual doses of sewage sludge. There was a reduction in yield and growth characteristics of sunflower in the second cycle; thus, additional fertilization with sewage sludge is recommended in each new cycle.